Antibacterial and Cytotoxic Bridged and Ring Cleavage Angucyclinones From a Marine Streptomyces sp - Guo, Lin; Zhang, Lu; Yang, Qiaoli; Xu, Bo; Fu, Xinzhen; Liu, Ming; Li, Zhi; Zhang, Shumin; Xie, Zeping (Frontiers in Chemistry, 2020)
Chemical investigation of a marine-derived Streptomyces sp. KCB-132, cultivated in liquid ISP2 medium, had led to the discovery of three C-ring cleavage angucyclinone N-heterocycles, pratensilins A–C, with a novel spiro indolinone-naphthofuran skeleton. Addition of 50 μM LaCl3 to the same medium and subsequent chemical analysis of this strain returned a new member of this rare class, pratensilin D (1), along with two new angucyclinone derivatives, featuring ether-bridged (2) and A-ring cleavage (3) structural properties. Their structures and absolute configurations were assigned by spectroscopic analysis, single-crystal X-ray diffractions, and equivalent circulating density (ECD) calculations. (+)- and (–)-1, a pair of enantiomeric nitrogen-containing angucyclinones, exhibited different strengths of antibacterial and cytotoxic activities.